Implementation of Hadith An-Nadhafatu Minal Iman in Environmental Da'wah at Former Madiun Residency - Uswatun Hanifa, Irma Rumtianing; Saputra, Agus Romdlon (MUHARRIK: Jurnal Dakwah dan Sosial, 2022)
The environment is one of the natural resources that means a lot for living things. But reality proves, many humans have not realized the importance of protecting the environment, especially in terms of efforts to preserve and maintain its cleanliness. Many even throw garbage in any place and consider it a normal thing. The teaching of cleanliness in Islam is a consequence of faith in Allah. Cleanliness is part of faith. Thus cleanliness in Islam has aspects of worship and morals. So the teaching of cleanliness should not only be a slogan, but must be made into a practical lifestyle, which educates humans to live clean all the time. Regarding the cleanliness of the environment, the Ponorogo, Madiun and Magetan governments have made several efforts in order to make people aware of the importance of maintaining environmental cleanliness by disposing of garbage in its place. These efforts include issuing local regulations governing waste management and sanctions for anyone who violates them, launching a plastic waste-free program, encouraging the realization of Adiwiyata schools, awarding Adipura trophies and providing as many trash bins in public places as possible.